2019
DOI: 10.21608/ejabf.2019.56733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crocus sativus aqueous extract (saffron) on Schistosoma mansoni worms in experimentally infected mice

Abstract: Saffron Granuloma Antioxidants Worm SEMThe present study is designed to evaluate the therapeutic effect of Crocus sativus(saffron) aqueous extract (CSE) alone or in combination with praziquantel on Schistosoma mansoni infected mice. Parasitological, immunological, pathological and immunohistochemical parameters and surface topography of worms were determined. Treatment of S. mansoni infected mice with saffron or PZQ revealed a significant reduction in worm burden, hepatic and intestinal ova count with a declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…El-Lakkany et al (2012) recorded that silymarin a product of artichoke lost to PZQ and the best results achieved when the extract was combined with PZQ. Also, Shaaban et al (2019) reported that anti-schistosomal effect of PZQ was more efficient than Crocus sativus aqueous extract alone. However, other herbs extract recorded antiparasitic effects as Pomegranata granatum, Commophora molmol extracts Allium sativum, A. cepa, Schitozim, Artemisia absinthium, Tanacetum parthenium, A. sativum clove, Zingiber officinale, , Lavendula dentata L., Thymus capitatus L. and T. bovei (El-Sherbini et al, 2009;Mantawy et al, 2011;El-Hela et al, 2013;Allan et al, 2014;de Almeida et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…El-Lakkany et al (2012) recorded that silymarin a product of artichoke lost to PZQ and the best results achieved when the extract was combined with PZQ. Also, Shaaban et al (2019) reported that anti-schistosomal effect of PZQ was more efficient than Crocus sativus aqueous extract alone. However, other herbs extract recorded antiparasitic effects as Pomegranata granatum, Commophora molmol extracts Allium sativum, A. cepa, Schitozim, Artemisia absinthium, Tanacetum parthenium, A. sativum clove, Zingiber officinale, , Lavendula dentata L., Thymus capitatus L. and T. bovei (El-Sherbini et al, 2009;Mantawy et al, 2011;El-Hela et al, 2013;Allan et al, 2014;de Almeida et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the worm's ability to select an appropriate attachment site during feeding is impacted by the elimination of the sensory papillae on the oral sucker (Reda et al, 2019). Additionally, tegumental damage may affect the tegumental functions, causing damage to the defensive mechanism in the worm, and therefore, it could be easily targeted by the host's immune system (Xiao et al, 2000;Kamel & El-Shinnawy, 2015;Shaaban et al, 2019).…”
Section: In Vitro Morphological Changes Of Male and Female Schistosom...mentioning
confidence: 99%